Kilmacreehy church, south chancel wall, tomb niche, tracery bar - O'Donovan, Danielle (My University, 2008)
Tracery bar from reconstructed tomb niche. Moulding comprises frontal fillet flanked at either side by hollow chamfer, quadrant and hollow chamfer. The rear of the tracery bar is rectangular.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Clare (Ireland)--Antiquities.; Tracery (Architecture); Funerary monuments; Late Medieval; roll moldings; moldings, hollow